ANALISIS BUKU “WHAT’S SO WRONG ABOUT YOUR SELF HEALING” DALAM PENERAPAN NILAI-NILAI SELF ACCEPTANCE - Rianty, Refina Okta; Yulia, Cici; Rahmah, Alyana Maulia; Rahmadina, Oktavia; Fajria, Fajria; Rahman, Alya Nur; Kirani, Putri Balqis (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2024)
Abstract: This research aims to provide information about the values of Self Acceptend contained in the book entitled "What's So Wrong Abour Your Self Healing" by Ardhi Mohammad. Self Acceptend or self-acceptance is an attitude where individuals are able to accept and know all their shortcomings and strengths and not demean themselves. The method used in this research is qualitative with the type of literature study research. In this book there are components in self-acceptance that are associated with the theory of Bastaman. The result of this research is that in this book there is a value that determines that a person can accept himself and can be applied in an individual's life, the aspects are Self Insight, Changing Attitude, Self Commitment, Directed Activities, Social Support.Keywords: Self Acceptend; Self-Potential; Self-Undersrtanding; Book Analysis.Abstrak: Penetitian ini bertujuan untuk memberikan informasi mengenai nilai-nilai Self Acceptend yang terkandung dalam buku berjudul “What’s So Wrong Abour Your Self Healing” karya Ardhi Mohammad. Self Acceptend atau penerimaan diri merupakan sikap dimana individu mampu menerima dan mengetahui segala kekurangan dan kelebihan diri dan tidak merendahkan dirinya sendiri. Metode yang dipakai dalam penelitian ini adalah kualitatif dengan jenis penelitian studi literatur. Dalam buku ini terdapat komponen-komponen dalam penerimaan diri yang dikaitkan dengan teori dari Bastaman. Hasil dari penelitian ini adalah bahwa dalam buku ini terdapat nilai yang menjadi penentu bahwa seorang sudah dapat menerima dirinya dan bisa diterapkan dalam hidup seorang individu, aspeknya adalah Pemahaman Diri (Self Insight), Pengubahan Sikap (Changing Attitude), Keikatan Diri (Self Commitment), Kegiatan Terarah (Directed Activities), dukungan Sosial (Social Support).